7th AIAA/USAF/NASA/ISSMO Symposium on Multidisciplinary Analysis and Optimization 1998
DOI: 10.2514/6.1998-4803
|View full text |Cite
|
Sign up to set email alerts
|

HSCT configuration design space exploration using aerodynamic response surface approximations

Abstract: A method has been developed to generate and use polynomial approximations to the range and cruise drag components in a highly constrained, multidisciplinary design optimization of a High Speed Civil Transport configuration. The method improves optimization performance by eliminating the numerical noise present in the analyses through the use of response surface methodology. In our implementation, we fit quadratic polynomials within variable bounds to data gathered from a series of numerical analyses of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The resulting optimum HSCT design configuration is plotted in Figure 6. The optimum design had a TOGW of 753,900 lbs and was similar to designs found in an earlier study [1] using a local optimizer. While more computational time was spent finding essentially the same design using the global optimizer as the local optimizer, an assurance was gained that the optimum found was the global optimum.…”
Section: Optimization Results and Parallel Performancesupporting
confidence: 63%
See 2 more Smart Citations
“…The resulting optimum HSCT design configuration is plotted in Figure 6. The optimum design had a TOGW of 753,900 lbs and was similar to designs found in an earlier study [1] using a local optimizer. While more computational time was spent finding essentially the same design using the global optimizer as the local optimizer, an assurance was gained that the optimum found was the global optimum.…”
Section: Optimization Results and Parallel Performancesupporting
confidence: 63%
“…The methods used to calculate the drag components used in the drag calculation and their corresponding ranges are described in [6], [7]. The aerodynamics calculations are based on the Mach box method [4], [3], and the Harris wave drag In previous work [1], it was observed that multiple optima exist within the design space. A visualization technique was needed to view the topology of the design space to understand the cause of the local optima, however the dimensionality of the design prevents traditional techniques from being used.…”
Section: Hsct Design Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…For present HCV concept, high aeroheating areas were stagnation point, wing leading edges and scramjet engine leading edges. Al-Garni et al 52 considered that, if K T w 1500 ≤ , all the heat would be radiated, so no active cooling was needed. We conduct a more severe constraint on aeroheating that surface temperature should be lower than K 1300 .…”
Section: Aeroheating Modelmentioning
confidence: 99%
“…The choice of gross weight as the objective function directly incorporates both aerodynamic and structural considerations, in that the structural design directly affects aircraft empty weight and drag, while aerodynamic performance dictates drag and thus the required fuel weight. This HSCT design problem is described in detail elsewhere (Baker et al (1998), Golovidov (1997, Hutchison et al (1993), Hutchison et al (1994), MacMillin et al (1996), MacMillin et al (1997)), and thus only a few pertinent details will be repeated here.…”
Section: Hsct Configuration Design Applicationmentioning
confidence: 99%